The Principle of Justice in The Dispute Between Hendy Irwanto Fong and KSP Indosurya Regarding Termination of Employment - Mikie Aditya Wicaksana; Iwan Erar Joesoef (Universitas Semarang, 2025)
This study analyzes the application of the principle of justice in efficiency-based employment termination disputes, focusing on Supreme Court Decision No. 1774 K/Pdt.Sus-PHI/2022 concerning the dispute between Hendy Irwanto Fong and KSP Indosurya. The increasing reliance on efficiency as a ground for termination, particularly during periods of economic crisis, has intensified tensions between business sustainability and the protection of workers’ rights. This research employs a normative juridical method using statutory, case, and conceptual approaches to examine judicial reasoning and its implications for substantive justice. The findings reveal that the Supreme Court prioritized procedural legal certainty by affirming the judex facti decision, while insufficiently addressing proportional fairness in the calculation and fulfillment of workers’ entitlements. The absence of complete material evidence, particularly regarding wage components, significantly weakened the worker’s claim and resulted in limited protection of substantive rights. This study demonstrates that formal compliance with procedural law often outweighs considerations of distributive and corrective justice, as articulated in Aristotelian justice theory. The novelty of this research lies in its dual contribution: practically, it formulates strategic guidance for drafting employment termination claims that are both formally valid and materially substantiated to strengthen workers’ access to justice; academically, it enriches labor law scholarship by integrating justice theory with judicial practice in Indonesian industrial relations disputes. The study concludes that achieving fairness in employment termination cases requires not only procedural compliance but also material completeness, judicial sensitivity to proportional justice, and institutional support to address evidentiary imbalances between employers and workers.